2020
DOI: 10.24272/j.issn.2095-8137.2020.076
|View full text |Cite
|
Sign up to set email alerts
|

Magnetic brain stimulation using iron oxide nanoparticle-mediated selective treatment of the left prelimbic cortex as a novel strategy to rapidly improve depressive-like symptoms in mice

Abstract: Magnetic brain stimulation has greatly contributed to the advancement of neuroscience. However, challenges remain in the power of penetration and precision of magnetic stimulation, especially in small animals. Here, a novel combined magnetic stimulation system (c-MSS) was established for brain stimulation in mice. The c-MSS uses a mild magnetic pulse sequence and injection of superparamagnetic iron oxide (SPIO) nanodrugs to elevate local cortical susceptibility. After imaging of the SPIO nanoparticles in the l… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
13
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
8
1

Relationship

4
5

Authors

Journals

citations
Cited by 21 publications
(14 citation statements)
references
References 41 publications
1
13
0
Order By: Relevance
“…While intracranial or deep brain MNP stimulation has mostly been validated with motor behaviors (55), these particles may be a valuable tool for creating and/or manipulating models of neuropsychiatric disorders (43,56). For instance, MNP stimulation of the prelimbic cortex reduced immobility in the forced-swim test and increased sucrose consumption in stressed mice (56). Rao et al (2019) demonstrated the use of MNPs for targeted drug delivery, where MNP-stimulated drug release increased dopamine-mediated social behavior.…”
Section: Discussionmentioning
confidence: 99%
“…While intracranial or deep brain MNP stimulation has mostly been validated with motor behaviors (55), these particles may be a valuable tool for creating and/or manipulating models of neuropsychiatric disorders (43,56). For instance, MNP stimulation of the prelimbic cortex reduced immobility in the forced-swim test and increased sucrose consumption in stressed mice (56). Rao et al (2019) demonstrated the use of MNPs for targeted drug delivery, where MNP-stimulated drug release increased dopamine-mediated social behavior.…”
Section: Discussionmentioning
confidence: 99%
“…LDH release assay. LDH contents were measured using LDH cytotoxicity assay kits as previously reported (47). The standards and culture supernatants were obtained and added into the appropriate wells (20 µl), matrix buffer (25 µl) and coenzyme I (5 µl) were sequentially added.…”
Section: Measurement Of Reactive Ox Ygen Species (Ros)mentioning
confidence: 99%
“…Furthermore, Li et al [ 91 ] intravenously injected magnetic nanoparticles with a core of Fe 3 O 4 in rats, which can enhance the therapeutic effect of TMS. Our research team constructed a novel superparamagnetic Fe 2 O 3 nanoparticle, accurately injected it into the left prelimbic cortex of CUMS mice treated by rTMS at10 Hz/0.1 T for 5 d, and significantly improving the depressive symptoms of these mice[ 92 ].…”
Section: Future Perspectivesmentioning
confidence: 99%